Addressing Adolescent Relationship Abuse in the Context of Reproductive Health Care - Ragavan, Maya I.; Barral, Romina L.; Randell, Kimberly A. (Seminars in Reproductive Medicine, 2022)
Adolescent relationship abuse (ARA) is a significant public health issue that includes physical, sexual, psychological and cyber abuse, reproductive coercion, and/or sexual exploitation within an intimate relationship in which one or both partners is a minor. ARA is associated with numerous negative outcomes that include all domains of health. Many negative outcomes of ARA are related to reproductive and sexual health (RSH); thus, reproductive health care providers must be equipped to recognize and address ARA. This article will review the epidemiology and outcomes of ARA, followed by a discussion of means to robustly address ARA in health care settings. We recommend a strengths-based approach that promotes healthy adolescent relationships, connects adolescents experiencing ARA to harm reduction resources, and equips adolescents to serve as a resource for their peers.
Keywords: adolescent relationship abuse; violence prevention; counseling; adolescent; reproductive health; sexual health